ORIENTASI DAKWAH ISLAM KEINDONESIAAN DAN AKTUALISASI NILAI-NILAI LOKAL - Sholikhin, Muhammad (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2009)
Abstract: In the midst of Islam’s universalism and its cultural hegemony, actually Islam in its applicationhave variations related with space and time of its people. Therefore, we have a duty to discern ourIndonesian- Islam discourse. At one side, Islam have universal dimension, free from local cultureinfluence, and on the other side, Islam have to present at the earth on its spreading and receiving byhuman being with its local content. Islam famous with its accommodative feature to local culture withbasic principle maintains old good ones, and takes new better ones. Ideal form of religious life isequilibrium state between symbolization and substance. Therefore, Indonesian-Islam didn’t lose itspreference as a part of a whole Islam